Development of The Notary Cyber Concept in Implementation of The Electronic GMS of Open Companies - Ikhsan Lubis; Duma Indah Sari Lubis (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2021)
The development of information and communication has affected various aspects of human life, and has affected the implementation of the duties of a Notary, who based on this authority will provide legal services to the community. Related to the implementation of the duties of a Notary, it is called an e-notary or also called a cyber notary. The use of technology in the digitalization era, therefore provides opportunities for digital transformation to facilitate interaction patterns in all aspects of life. a change in mindset (paradigm) in order to provide a positive response to opportunities for convenience, speed and accuracy of data accuracy. This information is expected to be the right concept for completing tasks, especially in the notarial field. The concept of a cyber notary through the latest platform can be connected directly to the internet network using an electronic media digitization system. Moreover, this system has developed as an integration of digital technology or digital transformation. That's why the author wrote this article.